Halal Certification in Bibliometric Perspective: Trend and Impact Analysis - Rafiqi, Rafiqi; Hastuti, Dwi; Hernando, Riski; Hendriyaldi, Hendriyaldi; Sukmawati, Nur (Jurnal Paradigma Ekonomika, 2024)
The era of globalization of the digital world has become a challenge for which the provision of goods and services to obtain labeling or recognition of healthy and halal foods is one in the field of food offered in stores, mini-markets, or supermarkets. This research builds on the previous dedication to halal; it also seeks to map the evolution of research on halal certification over an 18-year period, employing a bibliometric analysis approach with Dimension AI data. This in-depth examination of scientific literature and work on halal certifications aims to understand the concept and its evolution year by year. We collected the data by examining Article, Chapter, Monograph, and Proceeding publications, which yielded a total of 15,999 documents on halal certification published from 2007 to 2024. We evaluate the data using the VOSviewer software and classify it into three categories: network visualization, overlay visualization, and density visualization. The results show a considerable increase in publication of halal certification by 2023, which is 3,492 documents compared to the previous year. The trends among halal-based industrial research writers indicate that Fischer, Johan, is the most productive writer. According to keyword analysis, the most commonly used term in developing the trend of halal certification research is 'halal certification', followed by keywords related to review, effects, UMKM, and medium-sized enterprises. There are two countries that have made the largest contributions to halal certification research: Indonesia and Malaysia.